Population Study of Black Cormorants (Phalacrocorax sulcirostris) and Other Waterbirds in Kota Baru Bandar Kemayoran Bird Park, Jakarta - Mirza Dikari Kusrini (Department of Forest Resources Conservation and Ecotourism - IPB University, 1996)
This paper is the result of eight months research since November 1994 -June 1995, which is a part of hroaderresearch for the writer's master (S-2) thesis (on preparation). Research in three aqutic habitat (water reservoir,mangroves, and the mangrove-swamps boundary) had shown that most of the Black Cormorant population foundin the water reservoir areas. The number of the cormorant population is time fluctuated, with the highest numberfound on the 4th week of April (144 bird). Nineteen species of water birds and 2 species of fish eating teresterialbird were found, specifically 15 species of waders, 3 species of marsh hird , 1 species of seabirds and 2 species o lfish eating terrestrial birds. 'The number of species found relatively lower than the result of research conducted byMulyani and Pakpahan (1993) or Oni (1995) which were done on Febuary, March, April, May and August1994.The difference occurs because less area coverage and shorter observation time ( 12 hours in a day).